Inducing Different Neuronal Subtypes from Astrocytes in the Injured Mouse Cerebral Cortex - Mattugini, Nicola; Bocchi, Riccardo; Scheuss, Volker; Russo, Gianluca Luigi; Torper, Olof; Lao, Chu Lan; Götz, Magdalena (Neuron (Cambridge, Mass.), 2019)
Astrocytes are particularly promising candidates for reprogramming into neurons, as they maintain some of the original patterning information from their radial glial ancestors. However, to which extent the position of astrocytes influences the fate of reprogrammed neurons remains unknown. To elucidate this, we performed stab wound injury covering an entire neocortical column, including the gray matter (GM) and white matter (WM), and targeted local reactive astrocytes via injecting FLEx switch (Cre-On) adeno-associated viral (AAV) vectors into mGFAP-Cre mice. Single proneural factors were not sufficient for adequate reprogramming, although their combination with the nuclear receptor-related 1 protein (Nurr1) improved reprogramming efficiency. Nurr1 and Neurogenin 2 (Ngn2) resulted in high-efficiency reprogramming of targeted astrocytes into neurons that develop lamina-specific hallmarks, including the appropriate long-distance axonal projections. Surprisingly, in the WM, we did not observe any reprogrammed neurons, thereby unveiling a crucial role of region- and layer-specific differences in astrocyte reprogramming.